Comparison of Counter Pressure Massage and Hegu Point Cold Compress on Active Phase I Labor Pain - Reka Julia Utama; Ummu Aiman; Mahruri Saputra; Ferdi Riansya (Indonesian Journal of Global Health Research, 2024)
Labor pain can cause it weakness of the uterine muscles, obstruction of the birth canal and increased maternal anxiety. Anxiety can produce catecholamine hormones that cause tension in the pelvic muscles and affects the mother's pushing force during childbirth so that the pain increases and lengthens the delivery time increases the risk of maternal and fetal death. The purpose of this research is to determine the comparison of counter pressure massage (CPM) and Hegu point cold compresses for labor pain during the 1st active phase. The research method uses a randomized control trial design with two group pretest-posttest plan. Population in this study namely mothers who will give birth in the active phase of the 1st stage with the number of samples A total of 126 people were divided into 2 groups each CPM treatment and cold compresses will be given to the Hegu point. The measuring instruments used are the numerical pain rating scale (PNRS) and pain level recording sheets which have been proven valid and reliable, and have been widely used to measure pain levels. The analysis that will be used is univariate and bivariate analysis paired t test and independent t test. The results of the study showed that there was a difference in the intensity of labor pain during the first active phase before and after counter pressure massage (p=0.000) and cold compress at the hegu point (p=0.000). And there was no difference in the intensity of pain during the first active phase of labor between the counter pressure massage and cold compress groups in the Hegu point group (p=0.546>0.05). Cold compress counter pressure massage on the Hegu point is effective in reducing pain in the first stage of labor and counter pressure massage and cold compresses on the Hegu point group are equally effective in reducing labor pain.